Peningkatan Literasi Keuangan Siswa SMKS Bani Adna melalui Pelatihan Perencanaan Keuangan Pribadi Berbasis Excel - Septi Nurmalita; Putri Haryani; Siti Halizah Salsabilla; Ridho Rambu Bassae (Jurnal Bersama Pengabdian Kepada Masyarakat (SAMAMAS), 2025)
The low level of financial literacy among Indonesian youth remains a serious challenge, particularly for vocational high school (SMK) students who are being prepared to enter the workforce. This community service program aims to enhance students’ financial literacy through personal financial planning training using Microsoft Excel, conducted at SMKS Bani Adna, Bojong Loa Village, Tangerang Regency. The method employed was a one-day workshop consisting of three stages: a Google Form–based pre-test, an interactive training session emphasizing fundamental concepts of personal financial management and budgeting practices using Excel, and a post-test to measure students’ improvement in understanding. The training results indicated a significant increase in students’ financial understanding, with the highest improvement of 10.26% observed in the aspect of daily expense recording. A total of 93% of participants found the Excel template easy to use, and 89% expressed interest in joining follow-up training sessions. This program demonstrates that a simple technology-based approach can effectively enhance students’ financial literacy while offering opportunities for replication in other schools through collaboration among universities, schools, and local communities.